Stalino imperijos kova su Ukrainos sukilėlių judėjimu paskutiniajame Antrojo pasaulinio karo etape (1944–1945): Raudonosios armijos vaidmuo - Hrynevych, Vladyslav (Genocidas ir rezistencija, 2023)
This article, based on a wide array of archival documents, presents the analysis of military confrontation between the Stalinist Empire and the Ukrainian insurgent movement in Western Ukraine. Special attention is paid to the role of the Red Army, which, in addition to joint military punitive operations together with the NKVD itself resorted to organising anti-insurgency military measures and took an active part in such activities aimed at destroying the Ukrainian Insurgent Army (Ukraiinska povstanska armia – hereafter UPA) and the underground Organisation of Ukrainian Nationalists (hereafter – OUN) using such measures as deportation and resettlement of the local population from the front-line zone, military mobilisations and repressions against the families of UPA members. The author concludes that the war of the Red Empire against the Ukrainian national liberation movement embroiled significant masses of civilian population into its merciless millstones, which led to its barbarisation, so this war by its nature and devastating consequences can be considered in essence as the genocidal extermination of the Ukrainian people.
Keywords: World War II; Western Ukraine; UPA; Red Army; NKVD; genocide